2018
DOI: 10.1016/j.molcel.2018.05.033
|View full text |Cite
|
Sign up to set email alerts
|

mRNA Deadenylation Is Coupled to Translation Rates by the Differential Activities of Ccr4-Not Nucleases

Abstract: SummaryTranslation and decay of eukaryotic mRNAs is controlled by shortening of the poly(A) tail and release of the poly(A)-binding protein Pab1/PABP. The Ccr4-Not complex contains two exonucleases—Ccr4 and Caf1/Pop2—that mediate mRNA deadenylation. Here, using a fully reconstituted biochemical system with proteins from the fission yeast Schizosaccharomyces pombe, we show that Pab1 interacts with Ccr4-Not, stimulates deadenylation, and differentiates the roles of the nuclease enzymes. Surprisingly, Pab1 releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
260
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(284 citation statements)
references
References 60 publications
24
260
0
Order By: Relevance
“…Despite the utility of our mathematical model, it did not capture some finer details of mRNA metabolism. For example, it was not designed to model the burst of deadenylation that typically accompanies loss of each terminal PABPC molecule (Webster et al, 2018). However, when considering the aggregate behavior of multiple mRNAs from the same gene, these bursts become blurred, with some molecules in the burst phase and others between bursts.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the utility of our mathematical model, it did not capture some finer details of mRNA metabolism. For example, it was not designed to model the burst of deadenylation that typically accompanies loss of each terminal PABPC molecule (Webster et al, 2018). However, when considering the aggregate behavior of multiple mRNAs from the same gene, these bursts become blurred, with some molecules in the burst phase and others between bursts.…”
Section: Discussionmentioning
confidence: 99%
“…It should also be noted that PthA4 binds poly(U) RNA and is structurally related to PUF (pumelo and FBF) proteins, which recognize U‐rich sequences at the 3′‐end of mRNAs and are known to interact with CAF1 and recruit the CCR4‐NOT complex to modulate mRNA stability and translation (Goldstrohm et al , ; Filipovska and Rackham, ; de Souza et al , ; Van Etten et al , ; Wang et al, ). Thus, given that the CCR4‐NOT complex is a macromolecular machine that connects transcription elongation to translation (Babbarwal et al , ; Gupta et al , ; Villanyi et al , ; Webster et al , ; Yi et al , ), it seems reasonable to suggest that PthA4 could modulate its activity to enhance transcription and translation of citrus canker susceptibility genes.…”
Section: Discussionmentioning
confidence: 99%
“…The miRNA‐mediated deadenylation, on the other hand, required CAF1 deadenylase activity and its interaction with poly(A)‐binding proteins (PABPs) (Behm‐Ansmant et al , ; Fabian et al , ; Flamand et al , ; Piao et al , ). Importantly, recent studies in yeast using reconstituted CCR4‐NOT complex have revealed that while CCR4 is a general deadenylase that degrades PABP1‐bound poly(A) tails, CAF1 is required for the selective deadenylation of transcripts not bound by PABP1 and with lower rates of translation elongation (Webster et al , ; Yi et al , ). Thus, as new evidence emerges, the CCR4‐NOT complex has been regarded as a macromolecular structure that not only connects transcription to translation, but also determines the translational capacity of the cell during transcription elongation (Babbarwal et al , ; Gupta et al , ; Villanyi et al , ; Webster et al , ; Yi et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…These mRNA 3′ end modifications confer stability and translational efficiency to the transcripts (Bentley, ; Jalkanen, Coleman, & Wilusz, ; Proudfoot, ; Y. Shi & Manley, ). Conversely, removal of the poly(A) tail by deadenylation can signal mRNA decay and/or translational repression of poly(A) + transcripts (Aström, Aström, & Virtanen, ; Mayya & Duchaine, ; Nicholson & Pasquinelli, ; Webster et al, ; Yi et al, ; X. Zhang, Kleiman, & Devany, ).These modifications in the 3′ end are controlled by cis ‐acting elements present in the mRNA and trans ‐acting regulatory factors, such as RNA binding proteins (RBPs) and RNAs with complementary base‐pairing, such as, but not restricted to, microRNAs (miRNAs). For better understanding of basic aspects of 3′ end formation and its regulation, we suggest the reading of comprehensive reviews that have covered this topic (Hollerer, Grund, Hentze, & Kulozik, ; Neve, Patel, Wang, Louey, & Furger, ; Y. Shi & Manley, ).…”
Section: Introductionmentioning
confidence: 99%
“…Shi & Manley, 2015). Conversely, removal of the poly(A) tail by deadenylation can signal mRNA decay and/or translational repression of poly(A) + transcripts (Aström, Aström, & Virtanen, 1991;Mayya & Duchaine, 2019;Nicholson & Pasquinelli, 2019;Webster et al, 2018;Yi et al, 2018;X. Zhang, Kleiman, & Devany, 2014).These modifications in the 3 0 end are controlled by cis-acting elements present in the mRNA and trans-acting regulatory factors, such as RNA binding proteins (RBPs) and RNAs with complementary base-pairing, such as, but not restricted to, microRNAs (miRNAs).…”
Section: Introductionmentioning
confidence: 99%